2018
DOI: 10.3390/nu10081010
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity in Cambodian Garment Workers: The Role of Free Lunch Provision

Abstract: The objective of this paper is to compare food consumption by Cambodian garment workers with and without access to a free model lunch provision through a factory-based canteen. Data from an exploratory randomised controlled trial were analysed. In total, 223 female Cambodian garment workers were allocated to an intervention arm (six-month lunch provision) or a control arm. Dietary intake on workdays was assessed by qualitative 24-h recalls at baseline and twice at follow-ups during the period of lunch provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…of calories, one prerequisite to expect effects on anthropometry) through lunch provision might be restricted. Although skipping of breakfasts somewhat increased in intervention subjects, no significant differences in skipping breakfasts between groups were observed [19]. Yet, skipping of meals in workers with access to a staff canteen should be closely monitored.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…of calories, one prerequisite to expect effects on anthropometry) through lunch provision might be restricted. Although skipping of breakfasts somewhat increased in intervention subjects, no significant differences in skipping breakfasts between groups were observed [19]. Yet, skipping of meals in workers with access to a staff canteen should be closely monitored.…”
Section: Discussionmentioning
confidence: 88%
“…The study collected qualitative data on the dietary intake through 24 h-recalls among all participants at several interviews during the intervention [19]. Results indicate that some participants tended to skip breakfasts, but hardly ever skipped lunch meals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On provision of foods in the factories, randomized controlled trial findings 22 in Cambodia showed that although a free lunch resulted in more frequent consumption of dark green vegetables, vitamin A-rich fruits and other fruits, and oil and fat during lunch, it did not improve the dietary diversity sufficiently over a 24-h period. Recommendations were made to more closely adapt lunch to the nutritional situation of women and to monitor women skipping meals.…”
Section: Discussion and Implications For Programs And Policiesmentioning
confidence: 99%
“…In a previous research in Cambodia, a canteen offering low-price lunches ($1.00 USD) demonstrated potential to improve the food security of RMG workers. 22,23 The study assessed the nutritive value of a low-price lunch model and showed that the lunches satisfied energy and macronutrient recommendations but did not have enough iron. If meals are provided, attention to the quality and diversity of food is important to make health and productivity improvements.…”
Section: Discussion and Implications For Programs And Policiesmentioning
confidence: 99%